Immune checkpoint inhibitor-related colitis assessment and prognosis: can IBD scoring point the way? - Cheung, VTF; Gupta, T; Olsson-Brown, A; Subramanian, S; Sasson, SC; Heseltine, J; Fryer, E; Collantes, E; Sacco, JJ; Pirmohamed, M; Simmons, A; Klenerman, P; et al. (Springer Nature, 2020)
Background Immune checkpoint inhibitors (ICI) improve survival but cause immune-related adverse events (irAE). We sought to determine if CTCAE classification, IBD biomarkers/endoscopic/histological scores correlate with irAE colitis outcomes.